Heavy metals resistance bacteria in marine sediment of Pahang coastal water - Zainal Abidin, Zaima Azira; Chowdhury, Ahmed Jalal Khan (2016)
This study investigated the heavy metal resistance capabilities towards chromium (Cr), cadmium (Cd), nickel (Ni), copper (Cu) and cobalt (Co) of bacteria isolated from marine sediments of three locations, namely, Teluk Chempedak, Pantai Batu Hitam and Pantai Balok. Majority of the isolates from Pantai Balok area exhibited high resistance to Cr, Ni, Cu and Co with MIC >450 µg/ml and most isolates were found to be susceptible to Cd with highest MIC recorded 150 µg/ml. Meanwhile, isolates from Pantai Batu Hitam displayed high resistance to Cr and Ni (MIC >450 µg/ml) and a few isolates were found to show high resistance towards Co and Ni (MIC >450 µg/ml). However, almost all isolates from Teluk Chempedak were susceptible to all the heavy metals tested. Interestingly, there were a few isolates that displayed high resistance to Cd with MIC >450 µg/ml and this was not the case for isolates from Pantai Batu Hitam and Pantai Balok. Previously, these isolates were also found to have antibiotic resistance towards several antibiotics tested (vancomycin, tetracycline, streptomycin, penicillin G, ampicillin, rifampicin, polymyxin, chloramphenicol, erythromycin and gentamicin). Thus, this study illustrated that antibiotic resistance bacteria also possess heavy metal resistance capabilities. Further molecular identification will be conducted to confirm the identity of isolates that exhibited both antibiotic and heavy metal resistance capabilities. The presence of bacteria with both capabilities may indicate possible contamination of antibiotics and heavy metals residues in these areas which may pose a threat to the environment and human population if necessary actions are not taken immediately.